Investigation on the Compressive Behavior of Waste Rock Backfill Materials with Different Specimen Sizes for Roof Control - Meng Li; Shihao Xing; Peng Huang; Xiaobao Luo; Qiang Guo (Applied Sciences)
Waste rock backfilled into a goaf can function as the main load-bearing carrier to support the overlying strata, so the compressive behavior of backfill materials plays a critical role in the effectiveness of strata control. However, in the laboratory, the specimen size also significantly influences on the accurate prediction of compressive deformation in waste rock backfill materials. To assess the influence of the specimen size on compressive behavior in waste rock backfill materials, a WAW-1000D (Changchun Xinte Testing Machine Co., Ltd., Changchun, Jilin Province, China) electric servo-motor testing machine and self-made compressors of different sizes were used to characterize the compressive deformation of waste rock backfill materials with different specimen sizes. The stress–strain relationships and changes in the void ratio of specimens were analyzed, revealing the influence of the specimen size on the compressive behavior. The research found that when the ratio of the inner diameter of compressors to the maximum particle size of specimens is 15:1 and above, the inner diameter of compressors only has a slight influence. Taking a backfill panel in Xinjulong Coal Mine as the engineering context, waste rock with particle sizes in the range of 0~20 mm was backfilled. The measured roof subsidence was 568 mm, matching the measured experimental value. The results provide data to support roof subsidence predictions following waste rock backfill mining.